The Effect of Giving Virgin Coconut Oil Massage on Patients with Pressure Wounds in the Intensive Care Unit - Anindi, Ristia Siska; Rahayu, Sri (Indonesian Journal of Global Health Research, 2024)
Patients on bed rest in the ICU who experience pressure sores cause problems with skin and tissue integrity. As a result, the skin becomes dry, the wound becomes red and causes infection. This data raises nursing problems, namely disruption of skin and tissue integrity. The intervention of providing massage using Virgin Coconut Oil is a non-pharmacological therapy that is applied with the aim of preventing and reducing the incidence of pressure sores in patients who have been on bed rest for a long time. The aim of this research is to search for and analyze articles on the implementation of massage with Virgin Coconut Oil on bed rest patients with pressure ulcers in the ICU. This research method uses a literature review method through a data search base via search engines such as the Biomedic Database PubMed Google Scholar and Science Direct with the keywords namely ICU patients OR ICU Patients AND Virgin Coconut Oil OR VCO OR coconut oil AND pressure ulcer OR pressure sore were reviewed according to the PRISMA flow diagram. A total of 37 articles were found from searches using predetermined keywords then adjusted to the journal inclusion criteria. We found 6 journals that met the inclusion criteria and continued with review. The review process is carried out by analyzing the interventions carried out, the research methods used and the research results. The results of the review showed that pressure sores measured on the Braden scale by using Virgin Coconut Oil massage decreased compared to before. So, the results of this review can be a basis for health workers, especially nurses, to apply massage with Virgin Coconut Oil to bed rest patients to prevent pressure sores.